2001
DOI: 10.1016/s0168-6496(01)00178-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity within the equine large intestine as revealed by molecular analysis of cloned 16S rRNA genes

Abstract: The molecular diversity of the microflora present within the equine large intestine was investigated through the analysis of PCR-amplified 16S ribosomal RNA gene sequences. Total genomic DNA, recovered from samples of large intestinal wall tissue and lumen contents, was used to generate 272 random clones that were subjected to comparative phylogenetic analysis. The 272 sequences were classified into 168 operational taxonomic units/molecular species (at least 97% similarity), with 92% of recovered sequences bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
130
6
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(159 citation statements)
references
References 31 publications
16
130
6
7
Order By: Relevance
“…Horses are hindgut fermenters and derive 60-70% of their energy from VFAs, produced through microbial fermentation of soluble sugars and structural carbohydrates within the hindgut, which are absorbed across the epithelia of the large intestine (Daly et al, 2001). Thus, VFA concentrations can be used as indicators of intestinal health in the horse (Berg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Horses are hindgut fermenters and derive 60-70% of their energy from VFAs, produced through microbial fermentation of soluble sugars and structural carbohydrates within the hindgut, which are absorbed across the epithelia of the large intestine (Daly et al, 2001). Thus, VFA concentrations can be used as indicators of intestinal health in the horse (Berg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial ecology of foregut fermenters is researched extensively (Sylvester et al 2004;Denman & McSweeney 2006;Mosoni et al 2007;Wanapat & Cherdthong 2009). However, the literature regarding microbial ecology of hindgut fermenters is limited to horses (Koike et al 2000;Daly et al 2001;Yamano et al 2008). Results of present study serve as a baseline data for future research in this direction.…”
Section: Gut Microbial Profilementioning
confidence: 99%
“…More recent studies also refer to the specificity of this microbial population (Daly et al, 2001;Daly and ShiraziBeechey, 2003). Using molecular analysis, Daly et al (2001) reported that 89% of the recovered sequences did not correspond to any recorded ones, suggesting that the anaerobic microflora of the equine large intestine are underrepresented and that the equine flora may contain many novel bacterial species.…”
Section: Passage Ratementioning
confidence: 99%
“…Using molecular analysis, Daly et al (2001) reported that 89% of the recovered sequences did not correspond to any recorded ones, suggesting that the anaerobic microflora of the equine large intestine are underrepresented and that the equine flora may contain many novel bacterial species. In a latter study, Daly and Shirazi-Beechey (2003), using specific oligonucleotide probes, quantitatively analyzed the intestinal microflora and obtained the first data of predominant bacterial populations in the large intestine of horses.…”
Section: Passage Ratementioning
confidence: 99%
See 1 more Smart Citation